COVID-19 restrictions promoted the newly occurring loneliness in older people – a prospective study in a memory clinic population - Defrancesco, Michaela; Schurr, Timo A.; Hofer, Alex (Frontiers in Psychiatry, 2024)
Introduction: The COVID-19 pandemic was associated with high burden and numerous negative consequences for older people. Social isolation and loneliness are major and prevalent health problems impacting well-being and quality of life and may have increased due to pandemic-related restrictions. Methods: The present study investigate the impact of the COVID-19 pandemic on loneliness in people visiting a memory clinic between March 2020 and September 2022. We conducted a prospective, singlecenter, questionnaire-based observational follow-up study to assess potential predictors of newly occurring, pandemic-related loneliness. Next to a newly developed COVID-19 questionnaire, a comprehensive neuropsychological test battery, the Neuropsychiatric Inventory and the Geriatric Depression Scale were used.Results: In total 426 people (mean age: 76.48 years, 12.9% cognitively intact, 33.1% diagnosed with Mild Cognitive Impairment, 49.8% diagnosed with dementia, and 4.2% diagnosed with depression) completed the COVID-19 questionnaire at baseline and 166 at follow-up. Newly occurring loneliness was indicated by 22.3% of baseline participants and by 24.1% of follow-up participants. Results of logistic regression analysis showed that living alone (OR 5.452) and having less contact with friends (OR 2.771) were most predictive of the occurrence of loneliness. The use of digital communication media as an alternative strategy for social interaction was lowest in dementia patients (6-13%).Discussion: In conclusion, personal contacts and a close friendship network appear to be more decisive to prevent loneliness in older people than does the use of digital communication media. However, the use of digital communication media may be a useful addition to counteract loneliness in old age. useful to counteract loneliness, especially in dementia patients.